Management systems and soil use on fractions and stocks of organic carbon and nitrogen total in cerrado latosol - Geanderson Nascimento da Silva; João de Andrade Bonetti; Edicarlos Damacena de Souza; Helder Barbosa Paulino; Marco Aurélio Carbone Carneiro (Bioscience Journal, 2016)
Cerrado areas are agricultural frontiers of Brazil, being important to know the dynamics of carbon and nitrogen in agricultural production systems. The objective of this study was to evaluate the effects of management and soil use in fractions and stocks organic carbon and nitrogen in the Cerrado soil. The experiment was conducted in Latosol with four treatments: native Cerrado (CE), no-tillage 18 years (NT), coffee 10 years (CF) and integrated system for agriculture (ISA) three years, evaluating the fractions and stocks of organic carbon and nitrogen in three depths. Soil management systems, at all depths, were not able to recover the organic carbon, nitrogen and their stocks in relation to the Cerrado. In the surface layer there was a decrease in the organic carbon content of 21, 33 and 46% for NT, CF and ISA respectively. Also there was a reduction in the nitrogen content in the surface layer of 33, 36 and 59% for the NT, CF and ISA respectively. Organic carbon varied from 74.3 Mg ha-1 in the CE, 58.8 Mg ha-1 in NT, 56.4 Mg ha-1 in CF and 50.8 Mg ha-1 in ISA. It was concluded that the total organic carbon, nitrogen and its fractions were effective in demonstrating the effects of managements and soil use; that of no-tillage and coffee were not efficient in the recovery of stocks of carbon and nitrogen requiring managements with more carbon input and the integrated production system is still in consolidation process.